Socio-demographic profile of child and adolescent users of oral health services in Victoria, Australia - J Rodrigo; Hanny Calache; Martin Whelan (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to investigate the socio-demographic characteristics of the eligible population of users of public oral health care services in the Australian state of Victoria, aged 17 years or younger. The study was conducted as a secondary analysis of data collected from July 2008 to June 2009 for 45,728 young clients of public oral health care. The sample mean age was 8.9 (SD: 3.5) years. The majority (82.7%) was between 6 and 17 years of age, and 50.3% were males. The majority (76.6%) was Australian-born and spoke English at home (89.1%). The overall mean DMFT was 1.0 (SD: 2.1) teeth, with a mean dmft of 3.16 (SD: 5.79) teeth. Data indicate that, among six year olds in the Significant Caries Index (SiC) category, the mean dmft was 6.82 teeth. Findings corroborate social inequalities in oral health outcome and provide suggestions for oral health services to develop strategies and priorities to reduce inequalities in health and well-being, and better coordinate and target services to local needs.